Promotions Effectiveness of Kawah Putih Ecotourism by Perhutani’s Independenly Bussines Unit I - Menak Aryananda; Sambas Basuni; Tutut Sunarminto (Media Konservasi, 2017)
This research is intended to measure the effectiveness of the promotion of Wana Wisata Kawah Putih and the calculation of satisfaction, expectation and pereferensi of tourists managed KBM WIJAS 1 Perhutani. Campaign effectiveness can be measured using the EPIC model method. Epic model developed by AC Nielsen, measurement in terms of dimension, empathy, persuasion, impact and communication. Using quantitative methods, and using a sample of 100 respondents taken at random in Wana Wisata Kawah Putih Ciwidey Bandung. Respons to assess promotion of empathy, persuasion, impact and communication dimensions, satisfaction, expectations and preferences. The result of this research is the promotion of KBM Wijas 1 Perhutani rather effective in representing Wana Wisata Kawah Putih in Ciwidey. Satisfaction, expectation, and level of information preferences are very high on the promotion made by KBM WIJAS 1 Perhutani. Thus the results of the study is expected to be a reference for the development of KBM Wijas 1 Perhutani in Ciwidey to increase the number of visitors.Keywords: ciwidey, effective, epic, Perhutani, promotion